This preview shows page 1. Sign up to view the full content.
Unformatted text preview: a 6 = 0 ,Y = aX + b,so P ( Y y ) = P ( aX + b y ) = P ( X y-b a ) = F ( y-b a ) 2.1: 4. Solution: Let H = F + (1- ) G , then when x - ,H ( x ) whenx + ,H ( x ) 1. And since F and G are nondecreasing and right-continuous, so H is also nondecreasing and right-continuous. 1...
View Full Document
This note was uploaded on 12/25/2011 for the course MATH 543 taught by Professor Grant during the Fall '08 term at BYU.
- Fall '08